Digital Marketing Communication Model for Sustainable Jakarta LRT - Saleh, Nino Nopriandi; Setyawati, Endang (Jurnal Komunikasi Profesional, 2024)
This article has a look at the Jakarta Light Rail Transit (LRT) system's Digital Marketing Communication Model, highlighting the sustainable urban transportation. In view of the traffic gridlock and the pollution in cities, we need well-targeted communication strategies in promoting public transport.New studies in digital marketing, urban mobility, and sustainability is brought up to date. Everyone is heavily relying on digital platforms to convey information and change attitudes and behaviors towards the adoption of sustainable transportation solutions. The case studies of these strategies are then described using examples of similar urban locations. Meanwhile, an in-depth study was conducted through interviews with commuters, city planners, and marketing experts. A detailed research has been accomplished to find the main factors influencing acceptance and use of LRT by the public. The research results provide evidence for digital communications being the best way to get people to choose the Jakarta LRT. The document analyzes social media advertising targeted at specific groups of people, educational mobile apps, and activities such as community gatherings. The reader should agree with the view that the two-way interaction between the transportation authority and users should be continuous so that communication may be better and the challenges addressed. The communication gap can be best filled by transportation companies that choose the Digital Marketing Communication Model to make public transportation more sustainable. The platform offers the embedding of digital technologies into the ease of inherent sustainable urban mobility that would influence people in the more sustainable way to explore the merits of the Light train. This would then strengthen the communities discussing the use of electric buses, car-sharing schemes, and light rail transit-based transportation systems in relation to the city and the promotion of public transport facilities to people by informing them of the environmental benefits all these actions can bring.